A Rare Cause of Acute Abdominal Pain in Childhood: Peptic Ulcer Perforation - Ali Yurtseven; Mehtap Küçük; Zafer Dökümcü; Caner Turan; Eylem Ulaş Saz (Galenos Yayinevi, 2018)
Four children with a mean age of 12 years were referred to our emergency department with a history of abdominal pain. Examination revealed tenderness in the lower abdomen, in particular the left iliac fossa. The youngest child, who was 3 years old, also presented with shock. Abdominal X-rays revealed free air under both hemidiaphragms. Subsequent surgery was administered as the primary treatment of three patients and a partial resection was performed in the remaining one. The youngest child died and the others were discharged. These cases emphasize that although uncommon, alternate diagnoses must be kept in mind in children presenting with lower abdominal pain.